PELAKSANAAN ASAS PELAYANAN PUBLIK PADA PUSKESMAS SIMPANG BARU KOTA PEKANBARU - Tua F S, Harapan; syofian, syofian (Jurnal Niara, 2018)
Public services are the result of organizing organizations. Starting from all forms of activities in the arrangement, guidance, guidance, providers of facilities, services and others carried out by organizations engaged in the public sector. One public institution that organizes public services is the puskesmas while still paying attention to the principles of public service created by the institution in providing services to the community. The purpose of this study was to study the principles of service at the Simpang Baru Health Center, Simpang Baru Village, Tampan District, Pekanbaru City. The researcher uses a qualitative method that describes the implementation of the principles of public service by studying and studying the theory as a guide. Research informants are Puskesmas employees and the community as patients at Puskesmas with data collection techniques namely observation and interviews.